Two Fantastic Magic Lunettes - Wimmer, Norma [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2016)
Simplicio, the protagonist in Joaquim Manoel de Macedo's A luneta magica (1868), claimed to be doubly shortsighted: both physically and morally. For this reason he was taken to the shop of an Armenian who supplied him with magic lenses. These should enable him to better see the world and people. The pharmacist Hans Schnaps, from La lunette of Hans Schnaps (1859), one of the fantastic tales by Erckmann-Chatrian, creates a magic lens that can read people's thoughts. This comparative article seeks to evince the allegorical meaning of these two texts and the role of that magical object in them.
Keywords: A luneta magica; joaquim Manoel de Macedo; La lunette de Hans Schnaps; Erckmann-Chatrian; Fantastic